2003
DOI: 10.1109/tasc.2003.814027
|View full text |Cite
|
Sign up to set email alerts
|

Digital SQUIDs: New definitions and results

Abstract: Recently we found that several simple SFQ circuits (normally used as ADC comparators) dramatically outperform conventional SQUIDs in time resolution and slew rate. For example, it is possible to reach a resolution of about a few percent of flux quantum by using a single-shot measurement that takes only a few picoseconds. All these SFQ circuits produce during each clock period only one bit of information that indicates whether the applied flux is larger or smaller the threshold. As a result it is natural to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Sharp transitions of errors represented by dashed rectangles are caused by the hysteresis of the input-output characteristic of the SQUID loop. This phenomenon was discussed in detail by Haverkamp et al as the dead zone of the digital SQUID magnetometer [14]. These sharp transitions of the error can be deleted by careful circuit design and adjustment of the bias current supplied to the SQUID loop.…”
Section: High-sensitive Asynchronous Digital Squid Magnetometer mentioning
confidence: 98%
See 1 more Smart Citation
“…Sharp transitions of errors represented by dashed rectangles are caused by the hysteresis of the input-output characteristic of the SQUID loop. This phenomenon was discussed in detail by Haverkamp et al as the dead zone of the digital SQUID magnetometer [14]. These sharp transitions of the error can be deleted by careful circuit design and adjustment of the bias current supplied to the SQUID loop.…”
Section: High-sensitive Asynchronous Digital Squid Magnetometer mentioning
confidence: 98%
“…The digital SQUID carries out the digital feedback using a delta modulator. The digital SQUID magnetometers, in which dc-SQUID and superconductive single flux quantum (SFQ) circuits [11] are integrated at the low-temperature stage, have been proposed and implemented [12][13][14]. In the digital SQUID, SFQ circuits are used to control and measure SFQ pulses outputted by the dc-SQUID sensor.…”
Section: Introductionmentioning
confidence: 99%
“…The concept was brought by Rylov as early as in 1990 [21]. A detailed review of the last features and devices based on this concept can be found in [22]. A derived version of this design with some SFQ cells, like the comparator, replaced by their latching logic counterparts, that was more suitable regarding the clock frequencies in the MHz range, was experimentally demonstrated in 1995 by Yuh et al [23].…”
Section: From Conventional To Superconducting Digital Processing Of Smentioning
confidence: 99%
“…The idea of the circuit, proposed in [9], is to force a switching of two junctions on output (in particular and ) at each switching of . For one incoming pulse the phase across the output junctions jumps by , which corresponds to an average output voltage (1) with is the switching frequency of . In [10] the function of the voltage multiplier was demonstrated up to respectively a switching frequency of 125 GHz.…”
Section: The Whole Digital Squid Conceptmentioning
confidence: 99%
“…A Digital SQUID [1], based on RSFQ technique [2], [3], was presented by Semenov. Unfortunately the huge amount of Josephson junctions makes the realization in Low Temperature Superconductor (LTS) technology critical, in High Temperature Superconductor (HTS) technology almost impossible.…”
Section: Introductionmentioning
confidence: 99%